A Systemic Framework for Evaluating Computer-Supported Collaborative Learning—Mathematical Problem-solving (CSCL-MPS) Initiatives: Insights from a Colombian Case - Barros-Castro, Ricardo Abad; Córdoba-Pachón, José Rodrigo; Pinzón-Salcedo, Luis Arturo (Systemic practice and action research, 2014)
In general terms, computer-supported collaborative learning (CSCL) is a new educational paradigm that includes the use of technology to support learning activities. These CSCL environments can be used in a number of subjects (e.g. science, mathematics, language). As CSCL not only involves the implementation of technology or the design of online educational content, researchers have proposed inclusive models which highlight different dimensions of CSCL as a process. These models can then guide CSCL educators and designers improve the design, the experience, the management, and the evaluation of CSCL. However, the use of these models still needs to enable different CSCL stakeholders reflect on the values, purposes and impacts of their efforts. This paper presents a systemic framework that facilitates exploration of the inter-connections between the different aspects of CSCL, and enables a preliminary evaluation of its impacts in a particular context of application. The framework is then used to evaluate a Colombian CSCL project in the area of mathematical problem-solving (MPS). We report on the achievements of this project and in future possibilities to improve CSCL efforts in Colombia and elsewhere. These suggestions can help educators and other CSCL stakeholders to be sensitive and to respond to particular contextual conditions which can contribute to the success of CSCL initiatives.